2021
DOI: 10.1002/ps.6615
|View full text |Cite
|
Sign up to set email alerts
|

Density thresholds and the incorporation of biocontrol into decision‐making to enhance the control of Cacopsylla pyri in pear (cv. Ercolini) orchards

Abstract: BACKGROUND Economic injury level (EIL) and economic threshold (ET) are customary tools for integrated pest management. Cacopsylla pyri L. is a major pest in pear orchards. The aim of this work was to establish EIL and ET for the optimization of the use of insecticides to control this psyllid, considering biocontrol and two spraying strategies (low‐toxicity versus broad spectrum chemicals). This research was conducted over 4 years in five commercial pear, cv. Ercolini, orchards in south‐eastern Spain. RESULTS P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…For summer generations leaf samples are taken (Burts and Retan 1973, Westigard et al 1979). Treatment thresholds for russet using spur and leaf samples are provided by Nottingham et al (2022b) for C. pyricola and Sanchez et al (2022) for C. pyri . Complications in sampling are caused primarily by seasonal changes in the spatial distribution of eggs and nymphs (Burts 1988, Stratopoulou and Kapatos 1992, Sanchez and Ortín-Angulo 2011).…”
Section: Pest Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…For summer generations leaf samples are taken (Burts and Retan 1973, Westigard et al 1979). Treatment thresholds for russet using spur and leaf samples are provided by Nottingham et al (2022b) for C. pyricola and Sanchez et al (2022) for C. pyri . Complications in sampling are caused primarily by seasonal changes in the spatial distribution of eggs and nymphs (Burts 1988, Stratopoulou and Kapatos 1992, Sanchez and Ortín-Angulo 2011).…”
Section: Pest Managementmentioning
confidence: 99%
“…This information in turn is helping to develop integrated pest management programs that control psyllids with minimal disruption of the natural enemy community (Beers et al 2016, Shearer et al 2016, Amarasekare and Shearer 2017, Nottingham et al 2022b). Comparisons of psyllid control programs across commercial orchards in both Europe and North America have shown that substituting selective insecticides and biological control for conventional insecticides leads to conservation of natural enemies and to psyllid control (DuPont and Strohm 2020, DuPont et al 2021, Sanchez et al 2022).…”
Section: Pest Managementmentioning
confidence: 99%
“…This realization has prompted a slow shift into integrated programs in which selective insecticides, biological control, and cultural or horticultural practices are used as substitutes for high-toxicity psyllicides. A core tactic of these IPM approaches is to use practices that conserve natural enemies but which do not lead to economically damaging levels of psyllids [5][6][7][8][9]. Conservation practices include increased emphasis in monitoring of predators and parasitoids in orchards and in manipulating types, quantities, or timings of insecticides to minimize the effects of psyllicides on them [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Few economic thresholds explicitly incorporate natural enemy predation ( Zhang and Swinton 2009 , Shakya et al 2010 , Zhang and Swinton 2012 , Sanchez et al 2022 ). In some cases, pest mortality has been incorporated using life tables ( Ostlie and Pedigo 1987 , Barrigossi et al 2003 ), predation or parasitism estimates ( Hamilton et al 2004 , Musser et al 2006 ), or inaction thresholds (Sterling 1984).…”
Section: Introductionmentioning
confidence: 99%